Pengaruh Rasio Keuangan terhadap Harga Saham Perusahaan LQ 45 Periode 2011 - 2015 - Rita Widayanti; Fredella Colline (Bina Ekonomi, 2017)
This research aims to help investors in deciding how to invest in the stock market by analyzing the impact of company’s financial ratio on its share price. Financial Ratio used in this research are Current Ratio, Debt-Equity Ratio, Total Asset Turnover, Return on Equity, and Earning per Share as independent variables, and Stock Price as the dependent variable. This research employed the purposive sampling method using 18 samples of LQ45 companies which fulfilled the research criteria between 2011 – 2015 from 45 existing listed companies. This research employed Multiple Linear Regression analysis to test the hypothesis. The result shows that the Debt Equity Ratio and Earning per Share have significant influence on Stock Price, whereas Current Ratio, Total Asset Turnover, and Return on Equity do not have significant influence on stock price. Investors should review financial statements issued by the company and use financial ratios particularly Debt Equity Ratio (DER) and Earning per Share (EPS) as references in making an investment.Keywords: Current Ratio, Debt Equity Ratio, Total Asset Turnover, Return on Equity and Earning per Share, Stock Price